Varicella-zoster virus - Davison, Andrew. J. (Journal of General Virology, 1991)
Over the past 15 years or so, we have witnessed a dramatic increase in the generation of nucleic acid sequence data. The impact of this process has been felt particularly in animal virology, so that we now have complete genome sequences for representatives of most of the virus families. It is apparent that complete sequence determination of any virus genome is now a practical short or medium term goal. This is illustrated most clearly by the herpesviruses, whose large genomes have provided a challenge suited to serious genome sequencers. Thus, four complete herpesvirus sequences have been published to date. Those for Epstein-Barr virus (EBV) and human cytomegalovirus (HCMV) were derived at the MRC Laboratory of Molecular Biology in Cambridge, U.K. (Baer et al., 1984; Chee et al., 1990) and those for varicella-zoster virus (VZV) and herpes simplex virus type 1 (HSV-1) were obtained at the MRC Virology Unit in Glasgow, U.K. (Davison & Scott, 1986; McGeoch et al., 1988).